The photochemical reaction of Os 3(CO) 10(μ-H)(μ- γ-C 5H 3O 2), a triosmium cluster carrying a γ-pyrone ligand, with dimethylacetylenedicarboxylate: Formation of isomeric clusters - Lin, Q. (2014)
10.1016/j.jorganchem.2004.09.037